Impuesto al patrimonio vehicular y su contribución a la reducción de la contaminación del aire en la ciudad de trujillo, mediante su modificación - Castillo Gonzáles, Lita Alis (2013)
The purpose of the State is to provide the common good, one of their main duties is to protect the environment, for this must take various measures that usually materialize in legislation because of what it is to protect the environment by eliminating or at least reducing environmental pollution. Air pollution is a problem that has grown in the last decades and specifically in Trujillo city, which is largely generated by the automotive park, however the measures against this problem have not been entirely effective. For this reason, we performed the analysis of Article 30 of DS. No. 156-2004-EF "TUO of the Municipal Taxation Act" that regulates Vehicle Property Tax, a tax that only taxes the property of old and new vehicles for the period of three years from its first registration in Public Record. This investigation tries to determine whether the amendment of that article would help in reducing air pollution. This study is based on legislative and doctrinal analysis of Vehicle Property Tax and its various aspects, as well as environmental pollution and measures to combat it. Also resort to comparative law analysis of this tax in order to verify their regulation and the criteria taken into account. Also, in order to obtain the views of citizens who travels or works through the historic center of Trujillo city, was applied questionnaires obtaining relevant data for our research